Applying conversation analysis - Richards, Keith (Palgrave Macmillan, 2005)
This book explores the relationship between conversation analysis and applied linguistics, demonstrating how the analysis of institutional talk can contribute to professional practice. With a foreword by Paul Drew, the core of the collection brings together researchers from a wide range of applied areas, dealing with topics such as language impairment and speech therapy, medical general practice, retailing, cross-cultural training, radio journalism, higher education and language teaching and learning.